The Civil War chronicle - Sauers, Richard Allen (Legacy, 2004)
This in depth, chronological overview captures all the details and drama of the Civil War and its period. It explains the harsh realities of the four long and bloody years that ripped America to its core and helps you understand the incredible price that was paid for freedom. Hundreds of dramatic photographs and in depth captions presented in easy to follow chronological order, with a detailed timeline listing hundreds of items. Features biographical sketches of Abraham Lincoln, Jefferson Davis, Ulysses S. Grant, Robert E. Lee, and other prominent military and political figures, also includes sidebar essays about major battles and such other subjects as the underground railroad, the new technology of photography, the New York draft riots, and more.